2016
DOI: 10.22323/2.15030204
|View full text |Cite
|
Sign up to set email alerts
|

Understanding volunteer motivations to participate in citizen science projects: a deeper look at water quality monitoring

Abstract: Volunteer water quality monitors represent the intersection between citizen science and environmental stewardship. Understanding what motivates participation will enable project managers to improve recruitment and retention. This survey of 271 volunteers from eight water quality monitoring organizations in the U.S. found the strongest motivators to participate are helping the environment or community and contributing to scientific knowledge. No variation by gender was found, but younger volunteers have differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
108
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 17 publications
13
108
2
1
Order By: Relevance
“…What many studies show additionally is that participants have a high interest in science or the more specific project topic, as well as very positive attitudes towards science (Dean, Church, Loder, Fielding, & Wilson, 2018;Lynch et al, 2018). When it comes to people's age, results are more varied, ranging from samples mainly consisting of retired people (Alender, 2016) to more balanced examples (Dean et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…What many studies show additionally is that participants have a high interest in science or the more specific project topic, as well as very positive attitudes towards science (Dean, Church, Loder, Fielding, & Wilson, 2018;Lynch et al, 2018). When it comes to people's age, results are more varied, ranging from samples mainly consisting of retired people (Alender, 2016) to more balanced examples (Dean et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Being a member of a training group whose members went on to be more active in the FWW project also predicted higher retention. This association may have emerged if training with engaged peers leads to others becoming more engaged (Alender 2016, Laut et al 2017. Alternatively, people predisposed to engage with the project because of their personal motivations may have been more likely to attend training events with like-minded people.…”
Section: Discussion Volunteer Retentionmentioning
confidence: 99%
“…Since then, more studies have explored motivations of participants, usually through questionnaires. These studies have found that some of the important motivators are a desire to contribute to science, to help the environment (e.g., Hobbs and White 2012, Raddick et al 2013, Alender 2016, Domroese and Johnson 2017, or to learn (e.g., Domroese and Johnson 2017). In addition, some studies (such as Domroese and Johnson 2017) have found that social factors, such as a desire to participate with family or friends, are much less important motivators for most participants.…”
mentioning
confidence: 99%
“…For example, recent graduates have published their work on environmental education in prisons (Weber et al 2015), pollinators in prairie restoration (Buckingham et al 2016, Husby et al 2015, and volunteer motivations in environmental organizations (Alender 2016).…”
Section: Supporting Thesis Research Within An Interdisciplinary Framementioning
confidence: 99%